Nigerian English Varieties; The Sociolinguistic Perspective - Chioma , Eneremadu Queen Easther; Amam, Ndubuaku Rosita; Eziaku, Chukwuezi Emmanuela (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
Nigeria, which is a multi-ethnic society with different languages and cultures, has none of these indigenous languages accepted as the national languages among other reasons: one of which is The fear of domination of one ethnic group over the other. As a result of this, English language was accepted as the official language and given the pride of place over all other indigenous languages consequently, each of these ethnic groups uses the English language in a way to depict their culture and world- view, hence, English language tends to go through notarization, indigenization, etc, leading to different varieties (Nigeria English), this study discussed the varieties of Nigerian English from the sociolinguistic perspective. The first chapter introduced the study, the second reviewed the opinion of linguists on Nigeria English varieties (nev) the third showed the method of data collection, the fourth analyzed the findings while the fifth concluded the study and suggestions made for further studies.